PELAKSANAAN PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH INKLUSIF SDN 31 MATARAM TAHUN AJARAN 2021/2022 - Qurroti Ainin Nashof; Ahmad Hari Witono; Heri Hadi Saputra (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
The purpose of this study was to determine the implementation of Indonesian language learning at the Inclusive School of SDN 31 Mataram in the 2021/2022 Academic Year. This type of research is descriptive qualitative research. Data collection techniques used in this research are interviews, observation and documentation. The results of research regarding the implementation of Indonesian language learning in inclusive schools: a). The design of preparation for Indonesian language learning in inclusive schools is regulated in the form of a regular Learning Implementation Plan (RPP), the researchers found the results that the lesson plans for Indonesian language subjects had not been designed properly, the teacher did not include the Discovery Learning Model Syntax or the syntax of other learning models and there was no learning development activities oriented to Higher Order Thinking Skills (HOTS). b). The implementation of Indonesian language learning in inclusive schools is not carried out properly as evidenced by the way the teacher carries out learning activities consisting of the implementation of lesson plans, implementation of materials, implementation of methods, implementation of media, implementation of learning tools, and implementation of learning resources. c). Evaluation of online learning is not carried out properly as evidenced by seeing that the LKPD that has been made by the teacher is still incomplete and ineffective for Children with Special Needs (ABK). For this reason, the implementation of Indonesian language learning that was carried out was not effective to be applied in regular schools, namely SDN 31 Mataram.